Determining the Incidence of Asymptomatic SARS-CoV-2 Among Early Recipients of COVID-19 Vaccines (DISCOVER-COVID-19): A Prospective Cohort Study of Healthcare Workers Before, During and After Vaccination. (7th August 2021) - North, Crystal M; Barczak, Amy; Goldstein, Robert H; Healy, Brian C; Finkelstein, Dianne M; Ding, Delaney D; Kim, Andy; Boucau, Julie; Shaw, Bennett; Gilbert, Rebecca F; Vyas, Tammy; Reynolds, Zahra; et al.
Abstract: The impact of coronavirus disease 2019 vaccination on viral characteristics of breakthrough infections is unknown. In this prospective cohort study, incidence of severe acute respiratory syndrome coronavirus 2 infection decreased following vaccination. Although asymptomatic positive tests were observed following vaccination, the higher cycle thresholds, repeat negative tests, and inability to culture virus raise questions about their clinical significance.